Pelatihan Penerbangan Pesawat Drone Untuk Siswa SMK Al Farabi Medan - Andrian, Andrian; Agustina, Ika; Lubis, Reniwati; Anwar, Khairil; Aziz, Prily Fitria; Frianto, Herri Trisna (Unity Academy, 2024)
Unmanned aircraft or better known as drones have experienced rapid development in recent years. This technology has been used in various sectors, including military, agriculture, aerial photography, mapping, to surveillance and rescue. Along with the increasing demand and use of drones, skilled human resources are needed to operate and manage this technology safely and effectively. Lack of understanding of flight regulations, basic operating techniques, and drone maintenance can lead to the risk of accidents and violations of the law. Therefore, drone flight training for SMK Al Farabi Medan students is very important to ensure that drone operators have adequate competence. With this training, it is hoped that students can operate drones professionally, understand the technical and legal aspects involved, and be able to apply this technology optimally in their respective fields. This training also supports efforts to improve flight safety and more responsible management of drone technology.